Prediction of outcome in infants acute lymphoblastic leukemia by time to achievement of molecular remission - G. A. Tsaur; T. V. Nasedkina; A. M. Popov; O. V. Kalennik; A. G. Solodovnikov; T. O. Riger; Yu. A. Yakovleva; A. S. Ivanova; A. E. Druy; O. M. Plekhanova; E. V. Shorikov; L. I. Saveliev; et al. (Онкогематология, 2022)
Early therapy response is one of the major prognostic factors influencing an outcome of acute lymphoblastic leukemia (ALL).   The purpose of the given work was to define a time point (TP) of fusion gene transcript (FGt) monitoring by reverse-transcriptase PCR that clearly predicts outcome in infants with MLL-rearranged ALL, enrolled onto MLL-Baby protocol.   Molecular remission (cMR) was defined as absence of FGt at nested RT-PCR with sensitivity 1 × 10–4 or higher confirmed with negative result in the following time point (ТP). Detection of FGt in bone marrow (BM) was performed by qualitative nested RT-PCR on 15th , 36th and 43th days of therapy (TP1-TP3) and also during consolidation/intensification (ТP4-ТP9). Retrospectively, patients were divided into two groups. First group included 14 patients who achieved cMR by TP4, where two relapses occurred. The second group consisted of four MLL-AF4-positive patients, who did not achieve cMR by TP4. In this group there were 3 relapses. Number of relapses was significantly higher in the second group (odds ratio 18.00; 95 % CI: 1.19-271.47; p = 0.044). 6-years event-free survival (EFS) in the first group was 0.84 ± 0.10, in the second group — 0.25 ± 0.21 (p = 0.023). Cumulative incidence of relapse in the first group was 0.15 ± 0.01, in the second group 0.75 ± 0.08 (p = 0.022). Time of cMR achievement did not correlate with any known prognostic factors including therapy response on day 8, 15 and 36. Slow achievement of cMR corresponds to poor outcome in infant ALL with MLL rearrangements. Persistence of FGt at TP4 allows defining patients with high risk of relapse.